Towards a Methodology for Maturity Models Development: an Exploratory Study in Software Systems Interoperability Domain - Monteiro, Erasmo Leite; Mascarenhas, Ana Patrícia Fontes Magalhães; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Maturity models have been used in several domains to evaluate system maturity according to specific aspects. Despite their popularity, maturity models have been criticized due to lack of empirical validation and effective methods to aid in their definition. This paper presents our efforts to systematize the development of maturity models towards a methodology. In this direction, tasks, artifacts, methods, and tools related to maturity model definition were proposed and organized as an initial methodology to support developers. In addition, a maturity model, named Amortisse was developed applying the proposed methodology. The results of this investigation show the Amortisse Maturity Model and the methodology are feasible. We hope this methodology can help the definition of maturity models in different domains contributing to maturity models standardization.